Communication with Investors: Strengthening Strategies to Address the Decline in the Jakarta Composite Index and Improve the Welfare of MSMEs - Made Susilawati; Nadiya Yunan; Iswanto; Liza Utama (LP2M IAIN Palopo, 2026)
The volatility of the Jakarta Composite Index (JCI) in 2026 has created a precarious environment for both institutional investors and Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This research explores the pivotal role of strategic investor communication in mitigating the adverse effects of market downturns and its subsequent impact on MSME welfare. Utilizing a qualitative-exploratory approach, the study analyzes how transparent, data-driven communication strategies can stabilize investor sentiment and prevent capital flight during bearish periods. Furthermore, it investigates the structural link between capital market stability and the informal economy, particularly how fluctuations in the JCI influence the availability of credit and partnership opportunities for MSMEs. Grounded in Signaling Theory and Stakeholder Theory, the findings suggest that effective communication acts as a buffer against market irrationality. The research highlights that while a decline in the JCI often leads to tightened liquidity, proactive engagement strategies can sustain investor confidence in the long-term resilience of the Indonesian economy. This study concludes with a proposed framework for